ARSITEKTUR PALINGGIH ULAM AGUNG DAN PEDAU: ARTEFAK SIMBOLIK KEPERCAYAAN MASYARAKAT PESISIR NUSA PENIDA, DALAM OSMOSIS HINDUISME - Suyoga, I Putu Gede (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
The architecture of the palinggih ‘Balinese shrine’ is generally built based on the design of a sacred Hindu building according to the guidelines of traditional Balinese architecture, but different from the two architectural forms of shrines in Nusa Penida, Bali. This study focuses on the transformation of the belief system of Nusa Penida’s local coastal community belief system, which is realized into ulam agung (king of fish) and pedau (traditional sailboat) sacred buildings. The results of the study show that the transformation of the metaphor architectural shrine occurs because of the mastery, placement, and conversion of cultural, social, symbolic, and economic capital, that crosses individual and collective habitus in the realm of the Nusa Penida local coastal community belief system. The system of people’s belief in local gods undergoes a process of osmosis into gods in the pantheon of Hinduism. The socio-religious practice is also influenced by their level of knowledge, reasoning, and experience of the architectural form of the shrine as a symbolic Hindu religious building.